2007
DOI: 10.1007/s10709-007-9232-8
|View full text |Cite
|
Sign up to set email alerts
|

Microsatellite markers reveal high genetic diversity in date palm (Phoenix dactylifera L.) germplasm from Sudan

Abstract: Genetic diversity in date palm germplasm from Sudan representing 37 female and 23 male accessions was investigated using 16 loci of microsatellite (SSR) primers. Eight female accessions from Morocco were included as reference material. The tested SSR markers showed a high level of polymorphism. A total of 343 alleles were detected at the 16 loci. The number of alleles per marker ranged from 14 to 44 with an average of 21.4 per locus. A high level of expected heterozygosity was observed among Sudan cultivars (0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
72
6
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(96 citation statements)
references
References 24 publications
17
72
6
1
Order By: Relevance
“…Zehdi et al [17] reported similar results in their study on 101 date palm accessions from Tunisia, recording 134 alleles and 311 genotypes. However, the number of alleles in the current study was much lower (343) than those identified by Elshibli et al [15]. These differing results might be explained by variations in the degree of genetic diversity in the samples, resulting from a background of high sexual or backcross reproduction, which increases the level of diversity [48].…”
Section: Discussioncontrasting
confidence: 79%
See 1 more Smart Citation
“…Zehdi et al [17] reported similar results in their study on 101 date palm accessions from Tunisia, recording 134 alleles and 311 genotypes. However, the number of alleles in the current study was much lower (343) than those identified by Elshibli et al [15]. These differing results might be explained by variations in the degree of genetic diversity in the samples, resulting from a background of high sexual or backcross reproduction, which increases the level of diversity [48].…”
Section: Discussioncontrasting
confidence: 79%
“…There has been a clear increase in the application of the microsatellite technique (SSR) for date palm germplasms. For example, Elshibli et al [15] studied 37 females and 23 males from Sudan and Morocco.…”
Section: Introductionmentioning
confidence: 99%
“…Restriction fragment length polymorphisms (RFLP) were used for date palm cultivar identification (Corniquel and Mercier, 1994), however the technique was considered laborious and unsuitable for studying large numbers of samples. Other molecular markers including random amplified polymorphic DNA (RAPD) (Sedra et al, 1998;Soliman et al, 2003;Williams et al, 1990), inter simple sequence repeats (ISSR) (Hamza et al, 2013;Hamza et al, 2012), amplified fragment length polymorphism (AFLP) (Al-Khalifah and Askari, 2003;Cao and Chao, 2002;El-assar et al, 2005;Elassar et al, 2003); simple sequence repeat (SSR) (Ahmed and AlQaradawi, 2009;Al-Ruqaishi et al, 2008;Elsafi, 2012;Elshibli and Korpelainen, 2008;Pintaud et al, 2010;Zehdi et al, 2004;Zehdi et al, 2012;Zehdi-Azouzi et al, 2015;Zehdi-Azouzi et al, 2016), chloroplast DNA analysis (Sakka et al, 2013;Rhouma-Chatti et al, 2014) and inter-primer binding site (iPBS) (Al-Najm et al, 2016) were used to assess the genetic diversity of date palm germplasm collected from a variety of countries. Other researchers used a combination of these marker systems to study the genetic diversity of date palm germplasm (Abdulla and Gamal, 2010;Adawy et al, 2005;Hussein et al, 2005;Saker et al, 2006;Saker et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…A large study involving 37 female and 23 male accessions of date palm from Sudan, in addition to eight female cultivars from Morocco, concluded that high genetic diversity was revealed using 6 SSR markers (Elshibli and Korpelainen, 2008). The study detected a total of 343 alleles at the 16 loci, with an average of 21.4 (range from 14 to 44) alleles per locus, and reported a high level of expected heterozygosity for female (0.841) for male (0.799) cultivars from Sudan, and 0.82 for Moroccan cultivars.…”
Section: Microsatellites (Ssrs)mentioning
confidence: 99%
“…Therefore, traditional farmers should be encouraged to replant date palm orchards and home gardens with locally-produced, highly heterozygous and heterogeneous offshoots or seedlings. Replacement of old or dead date palm trees with only elite and foreign cultivars, as is the case in Egypt (Elkhishin et al, 2003), Tunisia (Hammadi et al, 2009;2011), and Sudan (Elshibli and Korpelainen, 2008; for example, will diminish genetic diversity and hasten genetic erosion of locally-adapted cultivars.…”
Section: Synthesis and Assessmentmentioning
confidence: 99%